Nirtetralin inhibits growth of hepatitis E virus in HepaRG cells - Zhang, Wu-Jing; Zhu, Ying-Bin; Zhang, Guo-Dong (Bangladesh Journal of Pharmacology, 2015)
Among numerous established in human hepatoma cell lines, none has been shown susceptible to hepatitis E virus (HEV) infection. Differentiation and infect ability are maintained but when these cells are cultured in the presence of corticoids and dimethyl sulfoxide. On exposure to the nirtetralin, the virion particles were found to be decreased with an IC50 of 2.277. Quantitative analysis of total and closed circular HEV RNA by real-time PCR performed on five independent experiments showed that only 1-5% of the HEV RNA internalized at day 1 post-infection entered the core of the cell refinement. The knockdown of 4E-BP1 led to a 1.7 ± 0.6-fold (mean ± SD, n = 5, p<0.01) and 2.4 ± 0.9-fold (mean ± SD, n = 4, p<0.05) (by the clone 56) growth of HEV RNA, respectively. Duncan's multiple range tests were applied to compare the differences between the treatment groups.